Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

2x-[4-3(2^5+18y)] simplify

Sagot :

= 2x - [4 - (96 + 54y)]
= 2x - 4 + 96 + 54y
= 2x + 54y + 92
[tex]2x-[4-3(2^5+18y)]\\\\=2x-[4-3(32+18y)]\\\\=2x-(4-96-54y)\\\\=2x-(-92-54y)\\\\=2x+92+54y[/tex]